The Impact of Cost-to-Income Ratio, Net Benefit, and Operating Expenses on Islamic Commercial Bank Loss Reserves - Annisa Anggraini; Fatih Fuadi; Is Susanto (Department of Islamic Banking, 2025)
Purpose – This study aims to examine the influence of Cost to Income Ratio (CIR), Net benefit (NI) and operating expenses operating income (BOPO) on the impairment loss reserve (CKPN). Methodology – In this study, the sample determination was carried out for 5 years. Determination of sample criteria using purposive sampling method, which is a sampling technique derived from certain criteria and obtained a sample of 6 banks so that the total number of samples is 30 samples. The method used is regression analysis of panel data using Random Influence Model approach analyzed through software Eviews 10. Findings – Derived from upshots of the study can be obtained that the partial Cost to Income Ratio has a significant influence on CKPN. Net rewards significant influence on CKPN. Operating expenses operating income has no significant influence on CKPN. Simultaneously Cost to Income Ratio, Net benefits and operating expenses operating income has a significant influence on CKPN in Sharia commercial banks registered with the Financial Services Authority for the period 2019-2023. In Islamic business management, efficiency (CIR and BOPO), transparency and benefit optimize halal income (NI) and maintain financial stability in accordance with sharia values. Implications – Upshots of this study provide recommendations to each bank in facing different credit risk challenges, both in terms of financing portfolio characteristics, risk mitigation strategies, and financial management policies. Originality – This study provides insight into the importance of risk management in Islamic banking, especially in managing impairment losses (CKPN) as a mitigation measure against potential financing risks.